Pengaruh Volume Usaha Dan Modal Sendiri Terhadap Laba Pada Koperasi Nurul Iman Dwiguna - Lesmana, Elsa Tianda; H Suwiryo, Darmo; Indrawan, Andri (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study aims to determine the effect of business volume and own capital on profits at the Nurul Iman Dwiguna Cooperative. The research methodology used is a quantitative method with an associative approach. The sampling technique used in this study was non-probability sampling with a total census sampling technique. Data collection techniques use secondary data types. While the data analysis technique uses parametric with the classical assumption test, regression analysis and hypothesis testing with the help of SPSS 25 software. The results of this study indicate that the volume of business has an effect on profit. Own capital has no effect on profits. Business volume and own capital have a simultaneous effect on profit. Therefore, the variables of business volume and own capital need to be considered by cooperatives because they can affect the profits of the Nurul Iman Dwiguna Cooperative.